ICT Self-Efficacy, Entrepreneurial Orientation and Technopreneurship Intention: A Single Mediated Model - Nurhayati, Dwi; Machmud , Amir; Suwatno (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to analyse the effect of ICT self-efficacy on technopreneurship intention that is mediated by entrepreneurial orientation. ICT self-efficacy is measured through computer self-efficacy and internet self-efficacy. Technopreneurial intention is measured through desire, preference, plans, and behaviour expectancies indicators. Entrepreneurial orientation is measured through inovative, proactive, and take risks. The research method used was the explanatory survey method, with data collection techniques through a questionnaire distributed to the young generation of Indonesia in the West Java region of 261 people from a population of 750 people. Data analysis techniques used descriptive statistics, inferential statistics, and regression analysis. The results of the study show that ICT self-efficacy has a significant effect on technopreneurship intention and entreprenreurial orientation mediates the relationship between ICT self-efficacy and technopreneurship intention. These findings imply that to improve technopreneurship intention will be more effective by increasing ICT self-efficacy and entrepreneurial orientation.